Diversity and Activity of Denitrifiers of Chilean Arid Soil Ecosystems - Orlando, Julieta; Carú, Margarita; Pommerenke, Bianca; Braker, Gesche (Frontiers in Microbiology, 2012)
The Chilean sclerophyllous matorral is a Mediterranean semiarid ecosystem affected by erosion, with low soil fertility, and limited by nitrogen. However, limitation of resources is even more severe for desert soils such as from the Atacama Desert, one of the most extreme arid deserts on Earth. Topsoil organic matter, nitrogen and moisture content were significantly higher in the semiarid soil compared to the desert soil. Although the most significant loss of biologically preferred nitrogen from terrestrial ecosystems occurs via denitrification, virtually nothing is known on the activity and composition of denitrifier communities thriving in arid soils. In this study we explored denitrifier communities from two soils with profoundly distinct edaphic factors. While denitrification activity in the desert soil was below detection limit, the semiarid soil sustained denitrification activity. To elucidate the genetic potential of the soils to sustain denitrification processes we performed community analysis of denitrifiers based on nitrite reductase (nirK and nirS) genes as functional marker genes for this physiological group. Presence of nirK-type denitrifiers in both soils was demonstrated but failure to amplify nirS from the desert soil suggests very low abundance of nirS-type denitrifiers shedding light on the lack of denitrification activity. Phylogenetic analysis showed a very low diversity of nirK with only three distinct genotypes in the desert soil which conditions presumably exert a high selection pressure. While nirK diversity was also limited to only few, albeit distinct genotypes, the semiarid matorral soil showed a surprisingly broad genetic variability of the nirS gene. The Chilean matorral is a shrub land plant community which form vegetational patches stabilizing the soil and increasing its nitrogen and carbon content. These islands of fertility may sustain the development and activity of the overall microbial community and of denitrifiers in particular.